Studi Literatur Dampak Penggunaan Gadget Bagi Perkembangan Kognitif Anak Usia Sekolah - Ni Komang Suri Rahayu; Ni Ketut Suarni; I Gede Margunayasa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Gadgets were communication tools used by various groups, both adults and children. School-aged children would experience growth and development, one of which would experience cognitive development. Excessive used of gadgets in children would had an impact on children's cognitive development. The aimed of this researched was to found out the impact of gadget used on the cognitive development of school-aged children. This researched used a literature studied or literature review method with the keywords the impact of gadget used and the cognitive development of school-aged children. The searched process was carried out via indexed electronic media such as google scholar. There were 7 articles that were relevant to the impact of used gadgets and 5 articles that were relevant to the impact of used gadgets on the cognitive development of school-aged children. The results of this literature studied were that gadgets greatly influence the cognitive development of school-aged children, both from the positive and negative sides. Lack of supervision from parents would had a negative impact on children's cognitive development, but if gadgets were used appropriately they would had a positive impact, namely improving the cognitive abilities of school-aged children.